INNOVATIVE APPROACHES TO CLUSTERING - Akhmedova Madina Shuhrat kizi (Innovate Conferences, 2025)
The development of cluster models plays a strategic role in ensuring economic growth and increasing the competitiveness of industries. Clusters not only contribute to job creation and the development of related industries but also strengthen innovation potential by enhancing the efficiency of production processes. In the context of globalization and intensifying competition, countries are actively implementing cluster models that optimize cooperation between enterprises, scientific centers, and educational institutions, improve access to advanced technologies, and stimulate investments in scientific research.